Using both clinical research and population-based cancer registry in long-term research- a case study using EORTC trials and the Dutch national cancer registry (IKNL). (June 2020) - Liu, Lifang; Neven, Anouk; Giusti, Francesco; Maraldo, Maja V.; Meijnders, Paul; Aurer, Igor; Fortpied, Catherine; Collette, Laurence; Visser, Otto
Highlights: Increased survival pleads for long-term follow up of key outcomes among patients treated for cancer. Data collection beyond end of trial is challenging due to operational and ethical constrains. Lacking of accurate treatment registration, registry-based studies often fail to draw causal relation between treatment and outcome. This single disease, single registry case study showed clearly the complementary features of clinical and registry databases. Collaborative proposals between clinical research and registries are put forward in long-term outcome research. Abstract: Objectives: There are more than 12 million long-term survivors of cancer in Europe. Yet, research on outcomes of cancer treatment has not reached its full potential due to operational, regulatory and methodological constrains. The current study aims to show the complementary roles between clinical research and population-based cancer registry in this research field. Methods: The authors used an empirical case study to show the level of agreement of variables between two databases of the same patients diagnosed with Hodgkin Lymphoma treated in the European Organisation for Research and Treatment of Cancer (EORTC) H1-H9 trials: one database is the clinical trial database from the EORTC and the other is the Netherlands Cancer Registry (IKNL). Results: The study showed a high level of agreement between the two datasets in most of the variables. However the vital status was more complete in the registry database, in particular for survivors diagnosed with cancer more than 10 years ago whereas treatment registration was more complete and in the EORTC clinical trial database. Conclusion: The current case study is based on one single disease area and one cancer registry, which needs further research to prove its feasibility in other settings. Nevertheless the authors have envisagedseveral actionable collaboration activities between clinical research organizations and population-based registries in long-term outcome studies in the future, including data linkage, joint methodology development, data quality cross-check and improvement program.